A randomized phase II trial of platinum salts in basal-like breast cancer patients in the neoadjuvant setting. Results from the GEICAM/2006-03, multicenter study - Alba-Conejo, Emilio; Chacón, J. L.; Lluc, A.; Antón, A.; Estévez, L.; Cirauqui, B.; Carrasco, E.; Calvo, L.; Seguí, M.A.; Ribelles, Nuria; Álvarez, R.; Sánchez-Muñoz, Alfonso; et al. (Springer, 2012)
Abstract Chemotherapy remains as the only systemic treatment option available for basal-like breast cancer (BC) patients. Preclinical models and several phase II studies suggested that platinum salts are active drugs in this BC subtype though there is no randomized study supporting this hypothesis. This study investigates if the addition of carboplatin to a combination of an alkylating agent together with anthracyclines and taxanes is able to increase the efficacy in the neoadjuvant treatment context. Patients with operable breast cancer and immunophenotypically defined basal-like disease (ER-/PR-/HER2- and cytokeratin 5/6? or EGFR?) were recruited. Patients were randomized to receive EC (epirubicin 90 mg/m2 plus cyclophosphamide 600 mg/m2 for 4 cycles) followed either by D (docetaxel 100 mg/m2 9 4 cycles; EC–D) or DCb (docetaxel 75 mg/ m2 plus carboplatin AUC 6 9 4 cycles; EC–DCb). The primary end point was pathological complete response (pCR) in the breast following the Miller and Payne criteria. Ninety-four patients were randomized (46 EC–D, 48 EC– DCb). pCR rate in the breast was seen in 16 patients (35 %) with EC–D and 14 patients (30 %) with EC–DCb (P value = 0.61). pCR in the breast and axilla was seen in 30 % of patients in both arms. The overall clinical response rate was 70 % (95 % CI 56–83) in the EC–D arm and 77 % (95 % CI 65–87) in the EC–DCb arm. Grade 3/4 toxicity was similar in both arms. The addition of carboplatin to conventional chemotherapy with EC–D in basal-like breast cancer patients did not improve the efficacy probably because they had already received an alkylating agent. These findings should be taken into consideration when developing new agents for this disease.
Este artículo ha sido publicado en Breast Cancer Research and Treatment Siguiendo las instruciones y dado que la revista dice que el artículo fue publicado tal cual se envió, hacemos un postprint copiando dicho texto enviado por la revista en un documento Word y luego convertido a PDF para así respetar el contenido, y sin dar acceso a los "extras" de la versión publicada. Esta versión tiene Licencia Creative Commons CC-BY-NC-ND
Keywords: Mamas - Cáncer - Tratamiento; Breast cancer; Neoadjuvant; Basal-like; Platinum salts